Inovasi Pelayanan Publik dalam Meningkatkan Kinerja Puskesmas Patimpeng di Kabupaten Bone - Anas, Ali; Murfat, Zulfitriani (Pencerah, 2023)
This research aims to find out the innovation of state civil apparatus in improving public service performance. Innovation in public services will be largely determined by a tradition that applies in an agency, building creativity, besides that the available space is often an obstacle to the creation of innovation ideas that are launched. This then becomes the focus of this research, namely innovation in improving the performance of public services. The idea of innovation is based on the slow service and the number of patients who lose their health cards, the limited number of patients who get services, namely 20 to 30 people a day. With the duration of medical record services previously 15 minutes after the innovation is not enough 5 minutes because the patient only mentions the house number. With administrative services until 15.00. This research was conducted at Patimpeng Health Centre, Bone Regency, which focuses on resource support, reward and punishment systems, organisational environment, budget support and personal based organisation as well as institutional strengthening in supporting the blessing innovations launched at Patimpeng Health Centre, Bone Regency. The research method used in this research is qualitative descriptive. The data collection process is interviews and documentation, and observation then the data obtained is reduced, coding the data to sort out the data in accordance with the indicators in the study and then drawing conclusions based on interview data, observation and documentation. The number of respondents in this study were 5 people consisting of puskesmas officers, the community and also the leadership of the Bone Regency health office. The results of this study found that the innovations carried out are still constrained by human resource support, budget limitations and also the understanding of the community regarding the new service system so that institutional strengthening still needs to be improved for the sustainability of these blessed innovations.